From Poverty, Inequality to Smart City Proceedings of the National Conference on Sustainable Built Environment 2015 - Seta, Fumihiko; Sen, Joy; Biswas, Arindam; Khare, Ajay (Springer Transactions in Civil and Environmental Engineering,, 2017)
This book is a comprehensive document visualizing the future of built environment from a multidisciplinary dimension, with special emphasis on the Indian scenario. The multidisciplinary focus would be helpful for the readers to cross-refer and understand others' perspectives. The text also includes case studies substantiating theoretical research. This method of composition helps the book to maintain rational balance among theory, research and its contextual application. The book comprises selected papers from the National Conference on Sustainable Built Environment. The chapters provide varied viewpoints on the core issues of urbanization and planning, especially in the economically diverse Indian market. This compilation would be of interest to students, researchers, professionals and policy makers.